2020
DOI: 10.1111/cdev.13466
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Sensitivity to Social Rewards and Punishments Moderates Link Between Peer Norms and Adolescent Risk Taking

Abstract: Although peer influence is a strong predictor of adolescents' risk-taking behaviors, not all adolescents are susceptible to their peer group. One hundred and thirty-six adolescents (M age = 12.79 years) completed an fMRI scan, measures of perceived peer group norms, and engagement in risky behavior. Ventral striatum (VS) sensitivity when anticipating social rewards and avoiding social punishments significantly moderated the association between perceived peer norms and adolescents' own risk behaviors. Perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 68 publications
5
33
0
Order By: Relevance
“…Yet our findings revealed that peer influence effects were equally strong across a broad range of behaviors and attitudes, suggesting that youth may be attuned to social processes nonspecifically, perhaps attending to social norms or their peers' perspectives in a broader way than previously assumed (e.g., even in the absence of (explicit) social reward). This idea is consistent with recent neuroscience research suggesting that influence and decision-making in social contexts may be associated not only with neural activity reflecting social reward processes (e.g., activation of the ventral striatum; Nook et al, 2015;Telzer et al, 2020) but also with the recruitment of social brain regions (e.g., dorsomedial prefrontal cortex; temporoparietal junction). For instance, regions involved in mentalizing indicate a general orientation and attunement to others (Telzer et al, 2018;van Hoorn et al, 2019).…”
Section: Examining Peer Influence Moderatorssupporting
confidence: 91%
“…Yet our findings revealed that peer influence effects were equally strong across a broad range of behaviors and attitudes, suggesting that youth may be attuned to social processes nonspecifically, perhaps attending to social norms or their peers' perspectives in a broader way than previously assumed (e.g., even in the absence of (explicit) social reward). This idea is consistent with recent neuroscience research suggesting that influence and decision-making in social contexts may be associated not only with neural activity reflecting social reward processes (e.g., activation of the ventral striatum; Nook et al, 2015;Telzer et al, 2020) but also with the recruitment of social brain regions (e.g., dorsomedial prefrontal cortex; temporoparietal junction). For instance, regions involved in mentalizing indicate a general orientation and attunement to others (Telzer et al, 2018;van Hoorn et al, 2019).…”
Section: Examining Peer Influence Moderatorssupporting
confidence: 91%
“…Relatedly, the present study focused on susceptibility with respect to the family context specifically. However, other important sources of social influence are critical in understanding the development of externalizing behavior in adolescents, especially including peer relationships (e.g., Telzer, 2016 ; Telzer et al, 2020 ;). It will be important for future studies to consider the unique and differential sources of social influence across adolescent development with respect to neurobiological susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Theories from the evolutionary developmental perspective, such as BSCT ( Boyce and Ellis, 2005 , Ellis et al, 2005 ) and the Differential Susceptibility Theory (DST; Belsky et al, 2007 ), converge to attribute children’s differential responses to neurobiological sensitivity to environmental inputs. A variety of behavioral and biological markers that reflect neurobiological sensitivity have been identified in existing literature, including behavioral phenotypes (e.g., difficult temperament or emotional reactivity; Cruz et al, 2018 ; Slagt et al, 2016 ), dopamine- and serotonin-related genes ( Bakermans-Kranenburg and Van Ijzendoorn, 2011 , Van IJzendoorn et al, 2012 ), psychophysiological stress responses ( Obradović et al, 2010 , Oshri et al, 2021 ), as well as neural signatures ( Liu et al, 2021 , Schriber et al, 2017 , Schriber and Guyer, 2016 , Telzer et al, 2021 ). Markers of heightened neurobiological sensitivity indicate children’s increased vulnerability to adverse environments, as well as elevated adaptive responses to positive early experiences ( Ellis et al, 2011 ).…”
Section: Translational Neuroscience Framework In Unpredictability Res...mentioning
confidence: 99%